2019
DOI: 10.1017/s0007114519000503
|View full text |Cite
|
Sign up to set email alerts
|

Starch digestion kinetics and mechanisms of hydrolysing enzymes in growing pigs fed processed and native cereal-based diets

Abstract: This study aimed to examine in vivo starch digestion kinetics and to unravel the mechanisms of starch hydrolysing enzymes. Ninety pigs (23 (sd 2·1) kg body weight) were assigned to one of nine treatments in a 3×3 factorial arrangement, with starch source (barley, maize, high-amylose (HA) maize) and form (isolated, within cereal matrix, extruded) as factors. We determined starch digestion coefficients (DC), starch breakdown products and digesta retention times in four small-intestinal segments (SI1–4). Starch d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…In our study, we observed a longer MRT of solid digesta in the SI of pigs fed IB compared with pigs fed GB. Numerically, the difference in MRT is largest in SI3 (Table 1), where the digestion coefficient of starch originating from GB (0•87) was lower than that of IB (0•96) (26) . Consequently, the longer MRT of IB seems to be caused by other components in the feed matrix than starch, which were mainly soyabean meal and soyabean hulls in the IB diet.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…In our study, we observed a longer MRT of solid digesta in the SI of pigs fed IB compared with pigs fed GB. Numerically, the difference in MRT is largest in SI3 (Table 1), where the digestion coefficient of starch originating from GB (0•87) was lower than that of IB (0•96) (26) . Consequently, the longer MRT of IB seems to be caused by other components in the feed matrix than starch, which were mainly soyabean meal and soyabean hulls in the IB diet.…”
Section: Discussionmentioning
confidence: 98%
“…This relation appears more complex in the case of solids, as the behaviour of the solid fraction of digesta depends greatly on the properties of the particulate matter. Compared with the diets with ground and extruded cereals, the diets with isolated starch were richer in soyabean hulls, soyabean meal and sugar beet pulp (26) . These ingredients generally have higher WHC than maize and barley meals (47) .…”
Section: Relation Between Digesta Properties and Gastric Mean Retentimentioning
confidence: 97%
See 3 more Smart Citations